Flies to Humans - Humans to Flies: A Virtuous Circle of Colorectal Cancer Prevention - Elena Kamilari; Yiorgos Apidianakis; Myrofora Panagi (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
The two Nobel prizes in physiology or medicine of 1995 and 2011 establish Drosophila genetics as a signifi cant contributor of genes and signaling pathways relevant to human disease, including innate immunity and cancer. Other than providing clues on mammalian gene homologue function, relatively little attention has been paid on the translational aspect of Drosophila genes, microbes and environmental factors that infl uence homeostasis and disease. This is particularly important for colorectal cancer (CRC) prevention, for which molecular diagnostic tools are non-existent. While clinical studies provide a wealth of information on genes and microbes linked to infl ammatory bowel disease (IBD) and CRC, it is unknown if they can serve as biomarkers in terms of CRC prevention. We discuss the line of research showing that many biomarkers of intestinal infl ammation and CRC in humans may be modeled and mechanistically tested in fl ies. Vise versa, genes and processes, such as regenerative infl ammation and aging- associated DNA damage, found in fl ies to promote tumorigenesis may be tested as biomarkers of CRC risk in humans. Thus, modeling human intestinal infl ammation and cancer in fl ies can provide a means to assess causality of conserved genes and microbes that can colonize the fl y intestine. Moreover, successful modeling in fl ies enables the "treatability" of the pertinent biomarkers via dietary, probiotic and pharmacological interventions and paves the way for clinical trials of treatments that may alleviate intestinal infl ammation and the risk for CRC.